2021
DOI: 10.1590/1519-6984.216198
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive evaluation, metabolisable energy and digestible amino acid contents of different indigenous feedstuff for Nile tilapia (Oreochromis niloticus)

Abstract: Three trials were executed to examine the nutritive profile, metabolisable energy and digestible amino acid (AA) contents of four indigenous feed ingredients including wheat (W), wheat middling (WM), canola meal (CM) and rapeseed meal (RSM) in Nile tilapia. Three samples of each test ingredient were collected from three different locations of Multan (MUL) and Sukkar (SKR), of Pakistan. The collected three samples were pooled thereafter to make a homogenous/ representative sample of each test ingredient from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…Regarding the other 17 amino acids, SLH presented a higher digestible composition only for leucine, phenylalanine, valine, cysteine, and tyrosine. The percentage of amino acids and coefficients of digestibility and, consequently, the value of digestible amino acids of the hydrolysates evaluated in the present study were higher than those found for the ingredients commonly used in the formulation of diets for Nile tilapia, including fish meal, canola meal, meat and bone meal, soybean meal, and protein concentrates and hydrolysates (Xavier et al, 2014;Vidal et al, 2017;Bibi et al, 2021;Cardoso et al, 2021). This result is attributed to the breakage of peptide bonds from proteins by enzymatic hydrolysis, which generates free amino acids or small peptides that improve nutrient bioavailability and use by the organism (Dieterich et al, 2014;Soares et al, 2020).…”
Section: Resultscontrasting
confidence: 59%
“…Regarding the other 17 amino acids, SLH presented a higher digestible composition only for leucine, phenylalanine, valine, cysteine, and tyrosine. The percentage of amino acids and coefficients of digestibility and, consequently, the value of digestible amino acids of the hydrolysates evaluated in the present study were higher than those found for the ingredients commonly used in the formulation of diets for Nile tilapia, including fish meal, canola meal, meat and bone meal, soybean meal, and protein concentrates and hydrolysates (Xavier et al, 2014;Vidal et al, 2017;Bibi et al, 2021;Cardoso et al, 2021). This result is attributed to the breakage of peptide bonds from proteins by enzymatic hydrolysis, which generates free amino acids or small peptides that improve nutrient bioavailability and use by the organism (Dieterich et al, 2014;Soares et al, 2020).…”
Section: Resultscontrasting
confidence: 59%